Richard Bösel, Antonio Camassa, Giovanna Spadafora. (a cura di). (2023). Andrea Pozzo. Teoria e prassi nel progetto architettonico della chiesa di Sant’Ignazio a Roma. Roma: Artemide. (diségno, 2023)
In Andrea Pozzo. Teoria e prassi nel progetto architettonico della chiesa di Sant’Ignazio a Roma, the editors –Richard Bösel, Antonio Camassa, and Giovanna Spadafora– collect sixteen contributions outlining the multifaceted figure of Andrea Pozzo, with particular attention on his work in the church dedicated to Saint Ignatius, the founder of the Society of Jesus. Andrea Pozzo dedicated his working life to painting, art, architecture, scenography, perspective, and the development of a treatise that collects his knowledge of these activities. The activities are all permeated by his deep faith dictated by his clerical status as a Jesuit lay brother. [read more]